A gift of dust : how Saharan plumes feed the planet - Brockenbrough, Martha (Alfred A. Knopf, 2025)
"From two award-winning creators comes a picture book that reveals the hidden wonders of how Saharan Dust impacts the world: from slowing a hurricane to nourishing a rainforest. This dust . . . of what lived once sustains what lives today and what will be born . . . tomorrow. An ancient catfish becomes a fossil, and as the lake where it lived dries up, the fossil turns to dust--but this isn't ordinary dust. This dust begins in Chad, West Africa, but winds carry it across the continent, over the Atlantic ocean, to nourish and replenish the Amazon rain forest and beyond. A Gift of Dust takes readers on a journey that shows just how interconnected our planet is, and how something so small can have such a huge impact. With lyrical, awe-inspiring verse based in fact, and stunning art from a Caldecott honoree, this is a story for our times"--